1995
DOI: 10.1007/bf00302069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of femoral rotation on bone mineral density measurements with dual energy X-ray absorptiometry

Abstract: Precision in femoral neck scans with dual energy X-ray absorptiometry (DXA) is affected by variability in positioning and subsequent repositioning of the femur for repeated scans. To study the in vitro effect of femoral rotation on the bone mineral density (BMD), four fresh-frozen cadaveric femurs were fixed in a specially designed jig which allows for rotation of the femurs. BMD measurements of the femurs were done in neutral position (0 degrees) i.e., with the femoral neck axis parallel to the surface of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 10 publications
0
30
1
1
Order By: Relevance
“…DEXA to measure BMD of the distal femur after TKA. Several authors have shown that the same problem exists for DEXA measurements of the hip with (Kiratli et al 1992, Gehrchen et al 1995, Mortimer et al 1996 and without (Girard et al 1994, Goh et al 1995) a hip stem implanted in the bone. To our knowledge no previous studies have evaluated the effect of rotation on the precision error when making DEXA measurements of the distal femur in patients with TKA.…”
Section: Discussionmentioning
confidence: 99%
“…DEXA to measure BMD of the distal femur after TKA. Several authors have shown that the same problem exists for DEXA measurements of the hip with (Kiratli et al 1992, Gehrchen et al 1995, Mortimer et al 1996 and without (Girard et al 1994, Goh et al 1995) a hip stem implanted in the bone. To our knowledge no previous studies have evaluated the effect of rotation on the precision error when making DEXA measurements of the distal femur in patients with TKA.…”
Section: Discussionmentioning
confidence: 99%
“…For scanning of the femoral neck the leg is slightly abducted and internally rotated, by use of a positioning device, to bring the femoral neck parallel to the scan table to avoid foreshortening of the femoral neck which would cause the BMD to be increased (same mineral content in smaller area of bone). Different leg positions can cause significant errors in BMD measured by DXA in the proximal femur (0.9 % to 4.5 % in the neck; 1.0 % to 6.7 % at Ward's area and 0.4 % to 3.1 % in trochanter) [35] and can be reduced by use of a positioning jig rather than the manufacturers' foot block [36]. For whole body scanning it is imperative that all parts of the body (including arms) are included in the scan field for precise results.…”
Section: Dual Energy X-ray Absorptiometry (Dxa)mentioning
confidence: 99%
“…1,3 Proper repositioning of the patients at each scan is vital to ensure reproducibility of the results. 1 Goh et al 14 showed that it was possible to reduce the error in the DEXA measurements by 50% by using a custom-made positioning jig rather than the manufacturer's own device. In our study we used this customised jig in all our patients.…”
Section: Percentage Change In Bmdmentioning
confidence: 99%